Mitigating ammonium and nitrate leaching in rice-wheat crop rotation: efficacy of neem coated urea and compost co-application - Kumar, Sandeep; Bhatia, Arti; Drewer, Julia; Rees, Robert M.; Sharma, Shikha; Kumar, Vinod; Tomer, Ritu; Rahman, Md. Mizanur; Sutton, Mark A. (Frontiers in Environmental Science, 2025)
IntroductionLeaching losses of applied N are an indirect source of nitrous oxide (N2O) emission, a major greenhouse gas emitted from fertilized soils. Mineral nitrogen (N) leaching research has largely concentrated on nitrate (NO3−), while ammonium (NH4+) leaching remains understudied. The cultivation conditions for rice and wheat are distinctly different, impacting the leaching losses of both NH4+ and NO3−.MethodsThis study investigated the influence of different N treatments, i.e., no-N control, neem coated urea (NCU-N 100%; 120 kgN ha-1), 60 kgN ha-1 Neem coated urea +30 kgN ha-1 compost (75% N); 90 kgN ha-1 Neem coated urea +30 kgN ha-1 compost (100% N) and 120 kgN ha-1 Neem coated urea +30 kgN ha-1 compost (125% N) in comparison with prilled urea (PU, 120 kgN ha-1). Compost was applied @ 2.6 tonnes ha-1 to all integrated treatments to provide 30 kgN ha-1.Results and discussionThe peak concentration of soil NH4+ and NO3− was delayed by two-three days in NCU and integrated NCU + compost compared to PU in both rice and wheat, due to the slow-release effect of neem oil coating in NCU. In rice, the percolation rate of water was almost half than in wheat soil. The mineral N leaching loss in rice ranged from 0.4 to 4.6 kg NH4+-N ha-1 and 0.46–5.12 kg NO3-N ha-1 during the 2 years. In an annual rice-wheat cycle, the total N leaching loss was 6.2%–7.0% of the applied N fertilizer. The total mineral N loss was higher in PU than NCU by 7.8% and 10% in rice and wheat, respectively. Substitution of 25% of mineral N with compost decreased the total N leaching by 14.8% and 10.3% in rice and wheat, respectively, compared to NCU (100%). The crop N uptake increased significantly (p < 0.05) with NCU and integrated NCU + compost (100%) over PU. Application of 125%-N significantly increased the total mineral N leaching. The total mineral-N leaching loss was 15.9% higher in rice than wheat across the different treatments. The integrated N application, combining 75% NCU and 25% compost, can reduce mineral-N leaching, improve nitrogen uptake and maintain economic yields in rice-wheat cropping system.